Linking Product Quality to Electric Vehicle Purchase Decision: The Mediating Role of Brand Image in Makassar - Muhammad Ilham Wardhana Haeruddin (PT. Maju Malaqbi Makkarana, 2026)
The purpose of this study is to examine how product quality influences consumers' decisions to buy electric cars in Makassar City, using brand image as a mediating factor. The swift expansion of electric vehicle adoption necessitates a comprehensive understanding of the factors influencing customer purchasing behavior in this nascent sector. A quantitative methodology utilizing an explanatory study design was implemented to examine the causal links among the variables. The population comprised consumers who had acquired or utilized electric vehicles in Makassar City, while the precise population size remained unspecified. A purposeful non-probability sampling strategy was employed, resulting in 105 respondents who completed a structured online questionnaire sent using Google Forms. The data were analyzed utilizing SEM-PLS with SmartPLS to investigate both direct and indirect effects among the constructs. The findings demonstrate that product quality positively and significantly impacts purchase decisions, product quality positively and significantly influences brand image, and brand image positively and significantly affects purchase decisions. Additionally, brand image serves as a partial mediator in the correlation between product quality and purchasing decisions. The findings indicate that superior product quality in electric vehicles is more influential in influencing purchasing decisions when it concurrently cultivates a favorable brand image in consumers' perceptions, thus offering strategic insights for manufacturers and distributors in formulating marketing strategies that enhance both product quality and brand image.